"The Triptan's Hangover": A Multicentric Cross-sectional Observational Study of the Adverse Events of Triptans in Patients With Migraine. Issue 2 (March 2022) - Rueda Vega, Mónica; Martínez-Fernández, Alicia; Quintas, Sonia; Díaz de Terán, Javier; Latorre González, Germán; Trabajos García, Olga; Vivancos Mora, Jose; Gago-Veiga, Ana Beatriz
Abstract : Abstract: The emergence of triptans represented a breakthrough in the treatment of migraine, but in clinical practice, patients describe symptoms that resemble those of a hangover after taking them. We propose the use of the Hangover Symptoms Scale (HSS) to evaluate this syndrome in patients that take triptans, which may help identify patients at higher risk of presenting these adverse effects that may interfere with therapeutic compliance. A cross-sectional observational pilot study with prospective data collection through a clinical-demographic questionnaire and the HSS was carried out on patients with migraine treated in headache units in 3 tertiary hospitals in Madrid. Sixty-six patients were included in the study. The median HSS was 4 and all symptoms were present in at least 15% of the patients, with difficulty to concentrate being the most frequent (57.6%). No significant differences were found between the presence of a higher HSS score and the sociodemographic characteristics of the patient or his migraine. The presence of aura was associated with a higher percentage of trembling ( P = 0.029) and fatigue (nonvisual, polymodal auras; P = 0.017). According to our study, triptans are responsible for a set of symptoms overlapping with those that occur during a hangover. Therefore, we propose that the HSS could be a useful tool for the evaluation and quantification of these effects in patients receiving triptans. In addition, we found that clinical features could be more frequently associated with the appearance of these adverse effects that, however, are not related to any particular patient profile.